The Role of the AGPAT2 Gene in Adipose Tissue Biology and Congenital Generalized Lipodystrophy Pathophysiology - de Melo, Maria Eduarda Cardoso; da Silva, Letícia Marques Gomes; Cavalcante, Ana Carolina Costa; Lima, Josivan Gomes; Campos, Julliane Tamara Araújo de Melo (International journal of molecular sciences, 2025)
1-Acylglycerol-3-phosphate O-acyltransferase (1-AGPAT) is an enzyme family composed of 11 isoforms. Notably, 1-AGPAT 2, the most studied isoform since its discovery, is a critical enzyme in the triglyceride synthesis pathway, converting lysophosphatidic acid to phosphatidic acid. In addition, AGPAT2 gene expression is shown to be essential for adipocyte development and maturation. Defects in AGPAT2 are responsible for significant pathophysiological alterations related to adipose tissue (AT). Pathogenic variants in this gene are the molecular etiology of Congenital Generalized Lipodystrophy type 1 (CGL1), in which fatty tissue is absent from birth. Metabolically, these individuals have several metabolic complications, including hypoleptinemia, hypoadiponectinemia, hyperglycemia, and hypertriglyceridemia. Furthermore, numerous AGPAT2 pathogenic variants that enormously affect the amino acid sequence, the tertiary structure of 1-AGPAT 2, and their transmembrane and functional domains were found in CGL1 patients. However, studies investigating the genotype–phenotype relationship in this disease are scarce. Here, we used bioinformatics tools to verify the effect of the main pathogenic variants reported in the AGPAT2 gene: c.366-588del, c.589-2A>G, c.646A>T, c.570C>A, c.369-372delGCTC, c.202C>T, c.514G>A, and c.144C>A in the 1-AGPAT 2 membrane topology. We also correlated the phenotype of CGL1 subjects harboring these variants to understand the genotype–phenotype relationship. We provided an integrative view of clinical, genetic, and metabolic features from CGL1 individuals, helping to understand the role of 1-AGPAT 2 in the pathogenesis of this rare disease. Data reviewed here highlight the importance of new molecular studies to improve our knowledge concerning clinical and genetic heterogeneity in CGL1.